Mixed Convection Flow Over An Exponentially Stretching/Shrinking Vertical Surface In A Hybrid Nanofluid - Ishak, Anuar; Waini, Iskandar; Pop, Ioan (Elsevier B.V., 2020)
The mixed convection flow and heat transfer over an exponentially stretching/shrinking vertical surface in a hybrid nanofluid is considered in this paper. Copper (Cu) and alumina (Al2O3) are employed as the hybrid nanoparticles while water as the base fluid. It is shown that the heat transfer rate enhances in the presence of nanoparticles. However, the reduction in heat transfer rate is observed for the shrinking case, caused by the imposition of stronger suction at the boundary. It is also found that the bifurcation of the solutions occurs for both stretching and shrinking regions as well as for both buoyancy aiding and opposing flows. The temporal stability analysis shows that only one of the solutions is stable and thus physically reliable as time evolves.